1985
DOI: 10.1152/jn.1985.53.6.1387
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic distribution of trigeminal nociceptive neurons in ventrobasal complex of cat thalamus

Abstract: Recordings were made from single thalamic units in the urethan-chloralose anesthetized cat. Altogether 2,905 trigeminal single units having a receptive field in the contralateral trigeminal integument were isolated from the somatosensory part of nucleus ventralis posteromedialis, or VPM proper. Each isolated unit was tested for responses to a series of mechanical stimuli. The stimuli included brushing the skin, touch, pressure, noxious pinch, and pinpricks. The majority of VPM proper units responded with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 0 publications
4
22
0
1
Order By: Relevance
“…Taking these results together, it may be assumed that nociceptive neurons are located in a shell-like fashion around the whole VB complex. We have confirmed that trigeminal as well as spinal nociceptive neurons were in fact located in a shell-like fashion around the ventrobasal complex consisting of the VPM proper and VPL [27,28]. We have called this marginal area the shell region of the VB complex.…”
Section: Nociceptive Neurons In Cat Vplsupporting
confidence: 64%
See 3 more Smart Citations
“…Taking these results together, it may be assumed that nociceptive neurons are located in a shell-like fashion around the whole VB complex. We have confirmed that trigeminal as well as spinal nociceptive neurons were in fact located in a shell-like fashion around the ventrobasal complex consisting of the VPM proper and VPL [27,28]. We have called this marginal area the shell region of the VB complex.…”
Section: Nociceptive Neurons In Cat Vplsupporting
confidence: 64%
“…Maxillary NS and WDR neurons occurred in the dorsomedial shell region, and mandibular NS and WDR neurons were found in the ventromedial shell region along the border between the VPM proper and VPMpc. In the caudal part of the NS zone only maxillary NS neurons were found in the dorsal shell region, whereas mandibular NS neurons were located in the caudal ventromedial shell region [28,30,31]. The distribution of trigeminal nociceptive neurons within the shell region of the VPM proper followed a pattern generally consistent with the somatotopic arrangement established for other somatosensory input to the VPM proper.…”
Section: Trigeminal Nociceptive Neurons In Cat Vpmsupporting
confidence: 57%
See 2 more Smart Citations
“…Guilbaud ๋“ฑ 15) ์€ ์œ ํ•ด ์ž๊ทน์— ๋ฐ˜์‘ํ•˜๋Š” ๋‰ด๋ก ์ด ์ฅ์˜ ๋ณต ํ›„ ์™ธ ์ธก ํ•ต ์„ ํ†ต ํ•ด ์‚ฐ ์žฌ ํ•œ ๋‹ค ๊ณ  ๋ณด ๊ณ  ํ•œ ๋ฐ” ์žˆ ์œผ ๋ฉฐ , Peschanski ๋“ฑ 17) ์€ ์ฅ ์‹œ์ƒ์˜ ๋ณตํ›„์™ธ์ธกํ•ต๋‚ด ์œ ํ•ด์„ฑ ๋‰ด๋ก ์ด ์œ ํ•ด ์ž๊ทน์˜ ์œ„์น˜, ๊ฐ•๋„, ์ง€์†๊ธฐ๊ฐ„์— ๋Œ€ํ•œ ์ •ํ™•ํ•œ ์ •๋ณด๋ฅผ ์ „ ๋‹ฌํ•  ์ˆ˜ ์žˆ๋‹ค๊ณ  ํ•˜์˜€๋‹ค. ๊ณ ์–‘์ด [18][19][20] ๋‚˜ ์›์ˆญ์ด 21) ์˜ ๋ณตํ›„๋‚ด์ธก ํ•ต์—์„œ๋„ ์—ญ์‹œ ๊ตฌ๊ฐ•์•ˆ๋ฉด๋ถ€์— ๊ฐ€ํ•ด์ง„ ์œ ํ•ดํ•œ ์ž๊ทน์— ๋ฐ˜์‘ํ•˜ ๋Š” ๋‹ค์ˆ˜์˜ ์œ ํ•ด์„ฑ ๋‰ด๋ก ์ด ์กด์žฌํ•œ๋‹ค๊ณ  ๋ณด๊ณ ๋˜์—ˆ๋‹ค. ํ•ด๋ถ€ํ•™์  ์—ฐ๊ตฌ์— ๋”ฐ๋ฅด๋ฉด ์ฅ์—์„œ ์‹œ์ƒ์˜ ๋ณตํ›„๋‚ด์ธกํ•ต์€ ๋ฐ˜ ๋Œ€์ธก ๋‡Œ๊ฐ„์— ์œ„์น˜ํ•œ ์‚ผ์ฐจ์‹ ๊ฒฝ ์ฃผ๊ฐ๊ฐํ•ต, ๊ทน๊ฐ„์†Œํ•ต ๋ฟ๋งŒ ์•„ ๋‹ˆ๋ผ ๋ฏธ์ธก์†Œํ•ต์œผ๋กœ๋ถ€ํ„ฐ ํˆฌ์‚ฌ๋ฅผ ๋ฐ›๋Š”๋‹ค 22,23) .…”
unclassified